2024
DOI: 10.1039/d3fo04395a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactiplantibacillus plantarum dy-1 fermentation on multi-scale structure and physicochemical properties of barley starch

Jiayan Zhang,
Yuhao Liu,
Mengting Liu
et al.

Abstract: The effects of fermentation on barley starch were studied using Lactiplantibacillus plantarum dy-1. The changes in multi-scale structure and physicochemical properties of barley starch were studied. The chain structure results...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In our previous research, Lactobacillus plantarum dy-1 isolated from pickles was found to change the composition of functional components and improve the nutritional value of barley via biological fermentation. 8,9 In these studies, oral administration of an aqueous extract of fermented barley with Lactobacillus plantarum dy-1 (LFBE) significantly prevented body weight gain and fat mass increase and improved lipid profiles and glucose tolerance in high-fat-diet induced obese male rats. 10,11 In addition, increased phenolic acids present in LFBE have been regarded as the key compounds for the lipid-lowering benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, Lactobacillus plantarum dy-1 isolated from pickles was found to change the composition of functional components and improve the nutritional value of barley via biological fermentation. 8,9 In these studies, oral administration of an aqueous extract of fermented barley with Lactobacillus plantarum dy-1 (LFBE) significantly prevented body weight gain and fat mass increase and improved lipid profiles and glucose tolerance in high-fat-diet induced obese male rats. 10,11 In addition, increased phenolic acids present in LFBE have been regarded as the key compounds for the lipid-lowering benefits.…”
Section: Introductionmentioning
confidence: 99%